Interviewing for Education and Social Science Research - Mears, Carolyn Lunsford. author. aut Link
XVII, 221 p.
Keywords: This volume introduces a fresh approach to research using a narrator-centred method, which provides a means for researchers to access the often hidden human responses about a situation so that those who make decisions and write policy may become better informed about the true impact of their actions on the individuals involved.